General Characteristics of patients with Primary Biliary Cholangitis from Türkiye and Denmark - Efe, Cumali; Batıbay, Ersin; Purnak, Tugrul (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Efe C, Batıbay E, Purnak T. General characteristics of patients with primary biliary cholangitis from Türkiye and Denmark. Turk J Gastroenterol. 2025;36(4):198-199.